Deconstruction of Indonesian Social Commerce Law: The Economic Democracy Perspective in Digitalization Era - Aditya Prastian Supriyadi (Jurnal Penelitian Hukum De Jure)
Social commerce (S-Commerce) comes from the disruption of business digitalization that explores social media. When s-commerce was developing, Indonesia banned the platform because it was considered to kill local businesses and capitalize on the market. The decision can potentially contradict economic democracy in one of the provisions of Article 33, paragraph (4) of the 1945 Constitution, which opens up technological space for developing the national economy. The purpose of writing this article is to deconstruct economic democracy on commercial law on social media as a Government policy that prohibits S-Commerce. The writing article uses normative legal research methods with statutory, legal comparison, and conceptual approaches. There are two research results in this article. First, at a time when significant nations are embracing technology at a rapid pace to boost their businesses, the government’s decision to outlaw s-commerce has negatively impacted the nation. Based on the doctrine of digitalization, economic law is not appropriate if it has to ban S-Commerce. The business paradigm of the contemporary era must be integrated with technology to compete with the development of the digital economy in the global realm. Second, based on economic democracy in Article 33, paragraph (4) of the 1945 Constitution, S-Commerce manifests a national economy balanced with technological progress by the constitution’s mandate. S-Commerce law provisions need to be deconstructed using the principles of economic democracy. So, reasonable legislative parameters may promote the growth of the digital economy while not jeopardizing the local economy.